2019
DOI: 10.1101/862292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrophil extracellular trap formation correlates with improved overall survival in ovarian cancer

Abstract: It is still a question of debate whether neutrophils, often found in the tumor microenvironment, mediate tumor-promoting or rather tumor-inhibiting activities. The present study focusses on the involvement of neutrophils in high grade serous ovarian cancer (HGSOC). Multi-omics data comprising proteomics, eicosadomics, metabolomics, Luminex-based cytokinomics, and FACS data were generated from ascites samples.Integrated data analysis demonstrates a significant increase of neutrophil extracellular trap-(NET) ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…For example, NET-S100A9-MMP9 acts as a critical component in connective tissue destruction (Akiyama et al, 2019). Levels of NET protein and S100A8 have also been shown to be important markers for predicting the prognosis of patients with ovarian cancer (Muqaku et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, NET-S100A9-MMP9 acts as a critical component in connective tissue destruction (Akiyama et al, 2019). Levels of NET protein and S100A8 have also been shown to be important markers for predicting the prognosis of patients with ovarian cancer (Muqaku et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, NETs were identified as an effector function of neutrophils, characterized by extracellular networks of chromatin coated with histones, myeloperoxidase, and neutrophil elastase (Colón et al, 2019;Zhang et al, 2020). Neutrophils carry out their physiological roles through mechanisms such as phagocytosis, degranulation, and the release of NETs (Muqaku et al, 2020). The process of NET formation has been identified as a novel form of neutrophil cell death known as NETosis (Cho and Cho, 2019;Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, chemotherapy induced neutropenia has also predicted improved survival rates among cancer patients [12][13][14][15][16][17], thereby raising important questions on the impact of neutrophils in tumor development. In the context of tumor metastasis, research has produced conflicting data in explaining whether neutrophils could promote the metastatic cascade [18][19][20][21][22], or support immune reactions inhibiting tumor growth [23][24][25][26]. A fuller understanding of the multifaceted neutrophil functionalities in tumorigenesis is still evolving [27], but there is a steadily growing appreciation that neutrophils can provide critical insights that are essential to tailor suitable anti-tumor and immunotherapeutic strategies, complementary to current therapeutic approaches [4,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%